RHO CASSIOPEAE - GIANT OR SUPERGIANT ? - Rosenbush, A. E. (Одеські астрономічні публікації, 2017)
Variable polarization of ρ Cassiopeae is found, with an amplitude of about 0.2 in the V band and up to 1 in R. It is drew attention on a conflict of luminosity from a spectral analysis (about -8 magnitude) and from a trigonometrical parallax (an average from four measurings corresponds to +0.5 magnitude). The paper submitted to Astronomische Nachrichten.